Social competencies of children with disinhibited social engagement disorder: A systematic review - Claire Davidson; Shahela Islam; Enrico Venturini; Anja Lowit; Christopher Gillberg; Helen Minnis (Wiley, 2024)
Abstract Background Children with Disinhibited Social Engagement Disorder (DSED) have specific difficulties with indiscriminate sociability, yet little is known about their broader social competencies as DSED tends not to be identified within samples in the wider 'maltreatment literature.' Aim To systematically review the literature to determine the social competencies of children with DSED. Methods A comprehensive search following PRISMA guidelines was undertaken using PsycINFO, Medline, Embase, and Cumulative Index to Nursing & Allied Health. Results From a total of 553 articles, 16 studies were selected and critically evaluated. Children with DSED were consistently reported to have poorer social competencies than non‐maltreated peers and environmental controls. Greater peer problems were consistently found, and they may present with poor self‐esteem/concept related to social acceptance. Findings regarding social interaction/communication skills were mixed. Limitations 50% of studies were of moderate quality due to sampling and possible confounding variables. Conclusion Children with DSED present with social relationship problems, beyond the core symptoms of the disorder, but the relative impact of co‐occurring neurodevelopmental conditions is not yet clear. In addition, pragmatic language and communication skills require further research.